Effect of elevated temperature to radiation shielding of ultra-high performance concrete with silica sand or magnetite - Rashid R.S.M.; Salem S.M.; Azreen N.M.; Voo Y.L.; Haniza M.; Shukri A.A.; Yahya M.-S. (Elsevier Ltd, 2023)
Deterioration; Magnetite; Silica; Silica sand; Ultra-high performance concrete; Elevated temperature; Shielding properties; Ultra high performance concretes (UHPC); Radiation shielding